In-situ nanodiamond to carbon onion transformation in metal matrix composites. (April 2018) - Suarez, Sebastian; Reinert, Leander; Zeiger, Marco; Miska, Patrice; Grandthyll, Samuel; Müller, Frank; Presser, Volker; Mücklich, Frank
Abstract: In the present study, nickel matrix composites reinforced with a fine distribution of nanodiamonds (6.5 vol%) as reinforcement phase are annealed in vacuum at different temperatures ranging from 750 °C to 1300 °C. This is carried out to evaluate the in-situ transformation of nanodiamonds to carbon onions within a previously densified composite. The resulting materials are thoroughly analyzed by complementary analytical methods, including Raman spectroscopy, transmission electron microscopy, scanning electron microscopy, energy dispersive X-ray spectroscopy and X-ray photoelectron spectroscopy. The proposed in-situ transformation method presents two main benefits. On one hand, since the particle distribution of a nanodiamond-reinforced composite is significantly more homogenous than in case of the carbon onions, it is expected that the transformed particles will preserve the initial distribution features of nanodiamonds. On the other hand, the proposed process allows for the tuning of the sp 3 /sp 2 carbon ratio by applying a single straightforward post-processing step. Graphical abstract: Image 1